Efficacy of vestibular rehabilitation and its facilitating and hindering factors from real-world clinical data - Kim, Min-Ku; Yun, So-Yeon; Lee, Seonkyung; Lee, Ja-Ok; Sung, Soo-Yun; Lee, Ju-Young; Kim, Hyo-Jung; Park, Hye Youn; Choi, Jeong-Yoon; Song, Jae-Jin; Choi, Byung Yoon; Koo, Ja-Won; et al. (Frontiers in Neurology, 2024)
Background and purpose Customized vestibular rehabilitation improved dizziness and imbalance in several randomized controlled trials. In the present study, we determined the efficacy of customized vestibular rehabilitation using real-world observational data. Methods In this retrospective observational study, we recruited 64 patients (median age = 60, interquartile range = 48–66.3) who completed the customized vestibular rehabilitation from January to December 2022. The outcomes of rehabilitation were evaluated using the dizziness handicap inventory (DHI) or vestibular disorders activities of daily living scale (VADL). The factors associated with outcomes were assessed with a generalized linear model, of which covariates included patients’ age, sex, duration of illness, type of vestibular disorders, initial DHI and VADL scores, exercise compliance, and initial hospital anxiety and depression scale (HADS) scores. Results After the median of 6 (4–6) weeks of rehabilitation, DHI and VADL scores significantly improved in patients with either peripheral or central vestibular disorders (Wilcoxon signed-rank test, p < 0.05). The initial DHI and VADL scores showed a positive while the sum of HADS scores showed a negative correlation with the outcome. In contrast, the age, sex, duration of illness, types of vestibular disorders, and exercise compliance did not affect the outcome. Discussion and conclusion Customized vestibular rehabilitation is effective for central as well as peripheral disorders, especially when the symptoms are severe and the psychological distress is mild.